2013
DOI: 10.1093/eurjhf/hft089
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between baseline and early worsening of renal function and efficacy of renin–angiotensin–aldosterone system blockade in patients with heart failure: insights from the Val‐HeFT study

Abstract: AimsWe evaluated the effect of (dual) renin -angiotensin -aldosterone system (RAAS) blockade with valsartan and an ACE inhibitor [92.7% of patients were treated with an ACE inhibitor in the Valsartan in Heart Failure Trial (Val-HeFT)] in patients with NYHA class II-IV heart failure (HF) and reduced EF on cardiovascular (CV) death and HF hospitalization by subgroups and by presence of early worsening of renal function (EWRF) and according to baseline estimated glomerular filtration rate (eGFR). Methods and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 33 publications
6
57
1
2
Order By: Relevance
“…19,20 WRF, evaluated as a time-dependent covariate in Cox proportional hazards models, was defined as a decrease of >20% in CrCl from the screening CrCl measurement at any time during the study period. This definition was recently used in several secondary analyses of randomized, controlled trials in patients with heart failure, [21][22][23] and it may be more accurate than an absolute increase in serum creatinine (ie, ≥0.3 mg/ dL), which could be biased by baseline renal function. 24 SRF was defined as the absence of WRF at any time.…”
Section: Definitions: Srf Versus Wrfmentioning
confidence: 99%
“…19,20 WRF, evaluated as a time-dependent covariate in Cox proportional hazards models, was defined as a decrease of >20% in CrCl from the screening CrCl measurement at any time during the study period. This definition was recently used in several secondary analyses of randomized, controlled trials in patients with heart failure, [21][22][23] and it may be more accurate than an absolute increase in serum creatinine (ie, ≥0.3 mg/ dL), which could be biased by baseline renal function. 24 SRF was defined as the absence of WRF at any time.…”
Section: Definitions: Srf Versus Wrfmentioning
confidence: 99%
“…First, we grouped the interventions that increased the risk for AKI (all were trials of dual or add-on reninangiotensin-aldosterone system [RAAS] blockade). [10][11][12][13][14][15][16][17][18][19][20] In total, 48,436 patients were enrolled in seven trials in this group. The mean follow-up time in these trials was 30 months, with a range of 11-56 months, and all were multicenter.…”
Section: Resultsmentioning
confidence: 99%
“…However, post hoc analysis of the Val-HEFT and EMPHASIS-HF Trials showed that, after the early decline in eGFR with dual RAAS blockade, there was no increased rate of eGFR decline over time as a continuous end point in the dual RAAS group to 3 years. 16,17 The data on long-term kidney function from the TOPCAT Trial will likely be forthcoming in the near future (the study was only recently published). Third, all interventions in the trials that were examined have multiple pathways of potential efficacy and harm.…”
Section: Discussionmentioning
confidence: 99%
“…7 Together, the findings in patients from the Americas enrolled in TOPCAT substantiate the concept that there could be a true pathophysiological continuum from HF-PEF to HF-REF involving cardiorenal interactions and response profiles similar to RAAS inhibition therapy, with increased rates of worsening renal function and hyperkalemia in patients from the Americas treated with MRA, albeit with better clinical outcomes. Similarly, although a serum potassium level >5 mmol/L has been shown to be associated with an increase in cardiovascular deaths in patients with HF-REF without or with chronic kidney disease, trials have shown that patients with HF-REF receiving an angiotensin-converting enzyme inhibitor, an angiotensin receptor antagonist, or an MRA (spironolactone or eplerenone) have better clinical outcomes despite experiencing more frequent episodes of hyperkalemia [8][9][10] and or worsening renal function 8,9 shortly after RAAS inhibitor initiation or thereafter. In HEAAL (Heart Failure End Point Evaluation of Angiotensin II Antagonist Losartan) 8 and EMPHASIS-HF (Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure), 10 high-dose losartan or eplerenone was associated with more frequent worsening renal function and hyperkalemia than low-dose losartan or placebo, respectively.…”
Section: Articles See P 34 and P 43mentioning
confidence: 99%